The effective removal of heavy metals from water by activated carbon adsorbents of Albizia lebbeck and Melia azedarach seed shells - Ullah, Mohib; Nazir, Ruqia; Khan, Muslim; Khan, Waliullah; Shah, Mohib; Afridi, Sahib Gul; Zada, Amir (Soil and water research, 2020)
The removal of toxic metals like lead (Pb) and cadmium (Cd) is very urgent keeping their hazardous effects in view. In this work, seeds of Albizia lebbeck and Melia azedarach trees were converted into activated carbon adsorbents and applied for the adsorptive removal of Pb and Cd metals from an aqueous solution. The as prepared adsorbents were characterised by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The removal efficiencies of both metals were strongly dependent on their initial concentration, contact time, pH, temperature and the quantity of adsorbents. 0.2 g of both adsorbents removed respectively 75 and 62% Pb and 77 and 66% Cd from from 100 ml of a 40 mg/l concentrated solution in 120 min at pH 5 and a temperature of 20°C. Both the Freundlich and Langmuir isotherms were well fitted to the experimental data. We believe that this work will provide a convenient way to synthesise low cost activated carbon adsorbents for the remediation of highly toxic metals from wastewater to safeguard our environment for future generations.